Chronotype, Sleep Quality and School Performance in adolescents- an integrative literature review - Araújo , Gabriele Lima de (2021)
This study aimed to investigate the association of chronotype with sleep quality and school performance of adolescents. An Integrative Review was carried out in which it was conducted according to the information collected in the Pubmed, Scopus and Embase databases, following the PRISMA guidelines . Observational articles were included, in English, Portuguese and Spanish, with no restriction on the period of publication, covering the age group from 10 to 19 years old and answering the leading question: “Is there an association of chronotype with sleep quality and school performance in teenagers? ” The descriptors ‘’chronotype”, “learning”, “Adolescent and its synonyms recognized by the vocabulary Mesch and Desc were used. 2625 articles were found, of which 2220 were selected for reading titles and abstracts. After this step 16 were selected for full reading, 5 articles were selected. Then, a manual search was performed in the reference of these articles, resulting in the inclusion of 8 more articles, totaling 13 articles to compose the qualitative synthesis of this review. It was found that afternoon chronotypes have more sleep-related disorders, emotional problems and poor school performance. There was an association of chronotype with sleep quality and school performance in adolescents. Adolescents with afternoon chronotype showed poor sleep quality, lower levels of attention and school performance, and greater risk of developing behavioral problems.